Based on quorum sensing: reverse effect of traditional Chinese medicine on bacterial drug resistance mechanism - Qiu, Ningning; Liu, Wenlong; Zhang, Xili (Frontiers in Cellular and Infection Microbiology, 2025)
Antimicrobial resistance has emerged as a critical global health challenge requiring urgent multidisciplinary interventions. Pathogenic bacteria utilize six principal resistance mechanisms: (1) Enzymatic degradation of antibiotics via the production of inactivating enzymes; (2) Inactivation of antibiotics by changing the drug targets; (3) Reduction of antibiotics entry by decreasing bacterial permeability; (4) Enhanced antibiotics efflux through overexpression of efflux pumps; (5) Acquisition of antibiotics resistance via genetic mutations; (6) Development of antibiotics resistance through formation of microbial biofilms. Notably, these resistance determinants demonstrate close coordination through quorum sensing, collectively establishing recalcitrant infections that defy conventional therapies. Emerging evidence confirms the therapeutic potential of traditional Chinese medicine in combating antimicrobial resistance. Traditional Chinese medicine can be used as quorum sensing inhibitors to interfere with the quorum sensing of bacteria, thereby achieving antibacterial effects. Moreover, traditional Chinese medicine has the characteristics of rich components, long history, mild action and no drug resistance, which makes it stand out in the research against drug-resistant bacterial infections. This paper systematically describes six mechanisms of bacterial resistance and reviews the antagonistic effects of traditional Chinese medicine against these mechanisms based on quorum sensing. It highlights that the active ingredients, extracts and compound formulations of traditional Chinese medicine have good reversal effects on bacterial antibiotic resistance, which can effectively treat drug-resistant bacterial infections. When combined with antibiotics, traditional Chinese medicine not only reduces antibiotics dosage but also adverse reactions, holding promise for improving and addressing clinical challenges posed by bacterial resistance. This article further discusses the impact of different delivery methods on the anti-bacterial biofilms efficacy of traditional Chinese medicine. It introduces the main delivery methods of traditional Chinese medicine at present and the new delivery methods under research, pointing out the huge development potential in the research of traditional Chinese medicine dosage forms. Additionally, the deficiencies and improvement methods of the current research were pointed out, and prospects for future related research were put forward.